2004
DOI: 10.1007/s00277-003-0777-z
|View full text |Cite
|
Sign up to set email alerts
|

Antierythropoietin antibodies in thalassemia patients

Abstract: We evaluated sera from 58 thalassemic patients for the presence of antierythropoietin antibodies to investigate whether these autoantibodies may relate with modest response to treatment with recombinant human erythropoietin (rhEpo). Thirty-seven patients had beta-thalassemia major, 9 patients had beta-thalassemia intermedia, and 12 patients had sickle/beta(+)-thalassemia. Of 58 patients, 24 were on rhEpo treatment in order to increase the intervals between transfusions or the hemoglobin (Hb) values. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In fact, cases which were positive only using MS-DAT, in which, unfortunately, eluates were not feasible as a first-step analysis, included patients suffering from B-CLL, myelodysplasia/aplasia, thalassemia intermedia, and hereditary spherocytosis (HS). Since mitogen stimulation induced autoantibody production and binding to autologous RBCs in culture, it is likely that MS-DAT is able to disclose latent anti-RBC autoimmunity in these diseases [11,22]. This could be of particular interest in B-CLL, where the negative prognostic significance of DAT positivity, even in the absence of AIHA, was demonstrated in a large prospective study [19].…”
Section: Discussionmentioning
confidence: 91%
“…In fact, cases which were positive only using MS-DAT, in which, unfortunately, eluates were not feasible as a first-step analysis, included patients suffering from B-CLL, myelodysplasia/aplasia, thalassemia intermedia, and hereditary spherocytosis (HS). Since mitogen stimulation induced autoantibody production and binding to autologous RBCs in culture, it is likely that MS-DAT is able to disclose latent anti-RBC autoimmunity in these diseases [11,22]. This could be of particular interest in B-CLL, where the negative prognostic significance of DAT positivity, even in the absence of AIHA, was demonstrated in a large prospective study [19].…”
Section: Discussionmentioning
confidence: 91%
“…Finally, antibodies to erythropoietin may contribute to an impaired ESA response. Such antibodies have been reported in patients with β-thalassemia and sickle/β(+)-thalassemia, 18 but may not be common among ESRD patients. 19 Future studies should investigate the prevalence of such antibodies in ESRD patients in relation to their hemoglobin phenotype.…”
Section: Discussionmentioning
confidence: 93%
“…Our group previously reported that HbAS hemodialysis patients exhibit an increase in red cell phosphatidylserine exposure. 25 Antibodies to erythropoietin have been observed in individuals with hemoglobinopathies, 26 and although not specifically studied in ESRD patients with hemoglobinopathy traits, they could reduce the effect of erythropoietin and ESAs. Inflammation is a feature of overt sickle cell diseases, and in ESRD it contributes to ESA resistance by blunting iron use and erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%